Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1200/jco.2022.40.16_suppl.5019
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of abiraterone (abi) combined with olaparib (ola) in patients (pts) with metastatic castration-resistant prostate cancer (mCRPC): Further results from the phase III PROpel trial.

Abstract: 5019 Background: The Phase III PROpel (NCT03732820) trial demonstrated at interim analysis a statistically significant clinical benefit from combining ola + abi in the first-line (1L) mCRPC setting vs placebo (pbo) + abi. Benefit was seen irrespective of a pt’s homologous recombination repair mutation (HRRm) status; median radiographic progression-free survival (rPFS) 24.8 for ola + abi vs 16.6 months for pbo + abi (hazard ratio [HR] 0.66, 95% confidence interval [CI] 0.54–0.81; P<0.0001). The safety profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Ultimately, only seven studies from the previous meta-analysis were selected. The characteristics of the selected studies are summarized in Table 1 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, only seven studies from the previous meta-analysis were selected. The characteristics of the selected studies are summarized in Table 1 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, only seven studies from the previous meta-analysis were selected. The characteristics of the selected studies are summarized in Table 1 [14][15][16][17][18][19][20]. Figure 2 presents a forest plot illustrating the impact of co-administration of PARP inhibitors.…”
Section: Re-analysis Of the Previous Meta-analysismentioning
confidence: 99%
“…Recently, some phase III clinical trials have shown the benefit of the combination of a PARPi with a new antiandrogen in the first-line setting of mCRPC. The PROpel trial [ 67 ] demonstrated an improvement in rPFS (HR 0.66 [95% CI 0.54–0.81]) of the combination of olaparib and abiraterone compared to abiraterone alone, irrespective of the HRR mutation status. On the other hand, preliminary results from MAGNITUDE showed the benefit of the combination of Niraparib and Abiraterone, with an improvement in the rPFS (relative risk 0.53, 95% CI: 0.36–0.79, p = 0.0014) and a reduction in the risk of disease progression/death (47% vs. 27%) in mCRPC with alterations in genes associated with HRR [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…This clinical trial [ 103 ] opens the door for a new horizon in PCa treatment. Actually, there is enough preclinical evidence that encourages the use of PARPi and RT [ 92 , 93 , 94 , 95 , 96 , 97 , 98 ]; abundant clinical evidence that supports the positive effect of combining PARPi and ADT [ 63 , 64 , 65 , 66 ] as well as PARPi and new antiandrogens [ 67 , 68 ]; and solid evidence for the use of RT and ADT [ 99 , 100 ]. So maybe it is time to explore the combination of the three therapies.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were not selected on the basis of biomarker criteria, suggested that they might benefit from the combination treatment irrespective of HRR mutation status (46). The PROpel study (47) presented at the 2022 annual meeting of the American Society of Clinical Oncology (ASCO) further demonstrated that olaparib plus AA, as the first-line therapy for mCRPC (including patients with HRR mutated and HRR-non-mutated), significantly prolonged rPFS in patients compared with the placebo plus AA group (24.8 vs. 16.6 months, P<0.0001). Preliminary results from the MAGNITUDE study (48) reported that niraparib plus AA significantly improved rPFS (relative risk 0.53, 95% CI: 0.36-0.79, P=0.0014) and reduced the risk of disease progression/death (47% vs. 27%) in the BRCA1/2 mutation subgroup of mCRPC.…”
Section: Clinical Research Progress Of Parp Inhibitors When Combined ...mentioning
confidence: 99%